The principles of commercial law - Nor Sa'adah Abd Rahman (Penerbit Universiti Teknologi Malaysia, 2011)
"The Principles of Commercial Law" provides a foundation on topics of law relating to commerce in Malaysia. This book includes a range of topics such as Malaysian Legal System, Law of Contract, and Law of Agency. Each of the chapters includes a discussion of cases and statutes relevant in the said area. This book is suitable for college and university students and the general public who are interested in obtaining basic legal knowledge in commercial law.